2019
DOI: 10.1055/a-0835-6806
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of a Novel Topical Herbal Composition (VEL-091604) Consisting of Gentian Root, Licorice Root and Willow Bark Extract

Abstract: The anti-inflammatory properties of the topical herbal composition VEL-091604 with gentian root, licorice root, and willow bark extract were assessed in a randomized, prospective, placebo-controlled, double-blind ultraviolet (UV)-erythema test study with 42 healthy volunteers in comparison to 1% hydrocortisone acetate. The efficacy and tolerability of VEL-091604 cream 2 times daily over 2 wk was evaluated in an open-label, prospective proof of concept study in 10 subjects with atopic dermatitis using a lesiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
10
0
2
Order By: Relevance
“…Furthermore it has been shown that a herbal composition with glycyrrhizinic acid (0.6%) and licorice extract (0.1% Glycyrrhiza uralensis root extract) as main active ingredients displays anti-inflammatory effects in a placebo-controlled double-blind UV-erythema test study 48 h after irradiation and cream application. The licorice-based product was as effective as 1% hydrocortisone acetate [17]. Besides, it reduced the severity score in 10 patients with AD treated twice daily over 2 weeks in a non-interventional pilot study [17] (LOE-B).…”
Section: Licorice (Glycyrrhiza Glabra (L))mentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore it has been shown that a herbal composition with glycyrrhizinic acid (0.6%) and licorice extract (0.1% Glycyrrhiza uralensis root extract) as main active ingredients displays anti-inflammatory effects in a placebo-controlled double-blind UV-erythema test study 48 h after irradiation and cream application. The licorice-based product was as effective as 1% hydrocortisone acetate [17]. Besides, it reduced the severity score in 10 patients with AD treated twice daily over 2 weeks in a non-interventional pilot study [17] (LOE-B).…”
Section: Licorice (Glycyrrhiza Glabra (L))mentioning
confidence: 97%
“…The licorice-based product was as effective as 1% hydrocortisone acetate [17]. Besides, it reduced the severity score in 10 patients with AD treated twice daily over 2 weeks in a non-interventional pilot study [17] (LOE-B).…”
Section: Licorice (Glycyrrhiza Glabra (L))mentioning
confidence: 97%
“…Among the oleanane-type triterpenes, glycyrrhizin, under the form of licorice extract, an ancient remedy for gastro-duodenal ulcers, was investigated for its wound healing potential in recurrent aphthous stomatitis; a controlled randomized double blind clinical trial evaluated the effect of licorice mouthwash containing diphenhydramine, results indicating a significant reduction in the severity of pain and healing time [184]. Licorice extract and glycyrrhizin in combination with gentian root and willow bark extract were also studied for their implication in atopic dermatitis in a clinical trial that enrolled 10 patients; the general observation was a strong reduction of the inflammatory process in the affected area, comparable with 1% hydrocortisone acetate treatment [185]. In another study, a combination of standardized extracts from Glycyrrhiza glabra, Thymus vulgaris, Vitis vinifera, Alpinia officinarum and Urtica dioica under the trade name Ankaferd blood stopper was reported to improve wound healing and promote hemostasis in gastro-intestinal bleedings [186].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) were isolated in Ficoll™ medium (Thermo Fisher Scientific, Waltham, MA, USA) and resuspended in RPMI 1640 medium supplemented with 1 % penicillin-streptomycin and 10 % foetal bovine serum (FBS) at a concentration of 1×10 6 viable cells/mL. The obtained cell cultures were then incubated with root extract at 37 °C for 48 and 72 h.…”
Section: Isolation and Cultivation Of Human Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%
“…It has a bitter taste due to the presence of triterpenoids, amarogentin and gentiopicroside in particular. Its extract contains many other bioactive compounds, such as xantones, flavonoids, and iridoids ( 1 , 3 ), some of which exhibit beneficial anti-inflammatory, antioxidative, radioprotective, immunomodulatory, and antimicrobial effects ( 2 , 4 , 5 , 6 , 7 ). Some reports suggest that the root extract has a potential to prevent and treat obesity, prevent insulin resistance and type 2 diabetes mellitus, and to mitigate cardiovascular complications, including atherosclerosis ( 8 , 9 , 10 ).…”
mentioning
confidence: 99%